TERTULIANO RADIOFÓNICO INSULTADO POR COMPAÑERO (A PROPÓSITO DE LA STS-CIV 236/2019 DE 23 ABRIL) - Sempere Navarro, Antonio (Revista de Derecho, 2020)
This study examines a dispute decided by the Civil Chamber of the Supreme Court, namely a claim for the protection of the right to honor brought by a particular radio journalist against another colleague. With this background, in a didactic way, we reflect on the type of contract between such professionals and the media. The ultimate aim is to encourage the interdisciplinary study of problems.
Keywords: right to honor; media professionals; spanish supreme court; employment contract; service contract; freedom of speech